Characteristics of simultaneous epoxy-novolac full interpenetrating polymer network (IPN) adhesive. Issue 7 (3rd April 2018) - Ahmed, Sabbir; Chakrabarty, Debabrata; Mukherjee, Subroto; Bhowmik, Shantanu
Abstract: In this investigation, an attempt has been made on the synthesis of epoxy-novolac IPN adhesive simultaneously by using full interpenetrating polymer network (IPN) technique. Novolac resin is mixed in different weight ratios with respect to epoxy resin. Thereafter, both the resins are cross-linked with their respective cross linker agents simultaneously. This epoxy-novolac IPN adhesive is characterized by various studies such as swelling; cross-link density; dynamic mechanical and thermal analysis and fourier transform inferred spectroscopy (FTIR). The swelling study reveals that the epoxy-novolac IPN adhesive is synthesized through full IPN technique successfully. The cross-link density result shows that epoxy- novolac (4:1) IPN adhesive has greater interpenetration than other epoxy-novolac IPN adhesive systems. Dynamic mechanical and thermal analysis (DMTA) result exhibits that epoxy-novolac (4:1) IPN adhesive is stiffer than another epoxy-novolac IPN adhesive system. The result of FTIR proves that epoxy-novolac IPN adhesive undergoes simultaneously. The results of all these characterization techniques conclude that epoxy-novolac IPN adhesive system with 4:1 ratio is considered to be the best IPN adhesive compared to others epoxy-novolac IPN adhesive systems.